A Highly Conductive Titanium Oxynitride Electron‐Selective Contact for Efficient Photovoltaic Devices. Issue 32 (1st July 2020) - Yang, Xinbo; Lin, Yuanbao; Liu, Jiang; Liu, Wenzhu; Bi, Qunyu; Song, Xin; Kang, Jingxuan; Xu, Fuzong; Xu, Lujia; Hedhili, Mohamed N.; Baran, Derya; Zhang, Xiaohong; et al.
Abstract: High‐quality carrier‐selective contacts with suitable electronic properties are a prerequisite for photovoltaic devices with high power conversion efficiency (PCE). In this work, an efficient electron‐selective contact, titanium oxynitride (TiO x N y ), is developed for crystalline silicon (c‐Si) and organic photovoltaic devices. Atomic‐layer‐deposited TiO x N y is demonstrated to be highly conductive with a proper work function (4.3 eV) and a wide bandgap (3.4 eV). Thin TiO x N y films simultaneously provide a moderate surface passivation and enable a low contact resistivity on c‐Si surfaces. By implementation of an optimal TiO x N y ‐based contact, a state‐of‐the‐art PCE of 22.3% is achieved for a c‐Si solar cell featuring a full‐area dopant‐free electron‐selective contact. Simultaneously, conductive TiO x N y is proven to be an efficient electron‐transport layer for organic photovoltaic (OPV) devices. A remarkably high PCE of 17.02% is achieved for an OPV device with an electron‐transport TiO x N y layer, which is superior to conventional ZnO‐based devices with a PCE of 16.10%. Atomic‐layer‐deposited TiO x N y ETL on a large area with a high uniformity may help accelerate the commercialization of emerging solar technologies. Abstract : TiO x N y films are demonstrated to be an excellent electron‐selective contact for both crystalline silicon and organic solar cells. Remarkable efficiency of 22.3% and 17.02% is achieved for crystalline silicon and organic solar cells, respectively.